An approach to teaching port management aided by a constructive modelling and simulation environment. (2016) - Balaban, Mariusz A.; Russell, Sara; Mastaglio, Thomas W.; Dykes, Paulette
A review of current literature has identified a gap in the use of constructive modelling and simulation (M&S) environments to teach port management skill sets. The fast pace of change in the maritime industry requires similar adaptation in post-secondary institutions. Old Dominion University (ODU) began development of a unique curriculum for a port management undergraduate course that integrates a geographic information system (GIS) based M&S environment with the traditional course curriculum. This paper explores theoretical framework, methodology, requirements and options for teaching port management aided by a constructive GIS-based M&S environment at ODU. A sample case study based on a real world problem is presented. Additionally, a survey was developed and administered to determine whether utilising a M&S tool gave students a better understanding of the course material and if they gained additional understanding through such a format as compared to classes where constructive M&S was not used. The results indicate that the use of constructive M&S can aid port management students to develop domain relevant problem solving skills, stimulate creativity, and critical thinking. The results provided should be generally applicable to other domains that involve management of complex systems like warehouses, hospitals, and manufacturing plants.